Utilization of dental care services among adult Indian population: A meta-analysis of evidence from 2011-2022 - Rounik Talukdar; Diplina Barman; Vallabh Thakkar; Suman Kanungo (Tabriz University of Medical Sciences, 2022)
Background: This study aimed to generate a pooled national estimate on dental health care services utilization by the adult population in India from any public or private facility in an effort to highlight the demand and usage for oral health care. Methods: In this meta-analysis, PubMed, ScienceDirect, DOAJ, and Google Scholar were searched using a search strategy that combined MeSH headings and keywords (e.g., "Oral Health", "Dental Health Services", utilization, India, etc.) for articles on dental utilization among Indian adults, published between January 2011 and June 2022. Study quality was assessed using the NIH Quality assessment tool, and a random-effects inverse-variance method was used for pulling utilization proportions. Meta-regression and sub-group analyses were conducted to identify the sources of heterogeneity. Heterogeneity is reported as I2 . To examine publication bias, the funnel plot, egger's test, and trim-and-fill analysis were performed. Results: From 4012 identified articles, 21 were eligible for inclusion. The pooled dental care utilization amongst Indian adults were found to be 23.96% (confidence interval [CI]: 16.81%- 31.11%, P<0.001, I2=98.93%), and the highest estimate was in South Zone (30.02%, CI: 19.14-40.90, P<0.01, I2=98.63%). Visual inspection of the funnel plot revealed the presence of publication bias (egger's P value 0.02). A mild decrease in utilization estimate was noted through trim and fill analysis (adjusted estimate 17.65%, CI: 8.97-26.33, P=0.03). No significant subgroup effect was found for the variables study zone and conduction years (P value: 0.09 & 0.34 respectively). Conclusion: Future studies should be undertaken to focus on the demand and supply of oral health care services since an evidential gap has been identified due to the uneven distribution of studies available from various regions of India. The heterogeneity can be attributed to the diverse socioeconomic, literacy, and inherent health system performance status.